Membangun Kepercayaan Konsumen Melalui Keaslian Influencer dan Autentisitas Pemasaran Digital - Aswira, Resfika; Kuswinton, Kuswinton (Jurnal Sekretaris dan Administrasi Bisnis, 2026)
This study aims to analyze the influence of influencer authenticity and digital marketing authenticity on consumer trust and its implications for purchase intention in the context of digital marketing. This study used a quantitative approach with data collection techniques through questionnaires distributed to respondents of SMKS Kesehatan Kota Baubau students. Data were analyzed using inferential statistical methods to test the relationship between variables. The results showed that influencer authenticity, consisting of the dimensions of sincerity, continuity, and integrity, had a positive and significant effect on consumer trust and purchase intention. In addition, digital marketing authenticity, which includes transparency, content realism, and message consistency, was also proven to have a positive and significant effect on consumer trust and purchase intention. These findings confirm that authenticity and transparency in digital communication are important factors in building consumer trust. Furthermore, consumer trust has been shown to play a major determinant in increasing purchase intention. This study implies that digital marketing strategies that emphasize authenticity can increase the effectiveness of marketing communications and encourage consumer purchasing behavior